Phytochemical study of Malaysian Uncaria cord at a var. Ferruginea (Bl.) RIDSD and its anti-hyperglycemic potential / Nur Hakimah Abdullah - Abdullah, Nur Hakimah (2016)
In this study, the chemical constituents and the in vitro anti-hyperglycemic potential of Malaysian Uncaria cordata var. ferruginea were studied. The phytochemical study of this plant led to the isolation often compounds comprising four different classes of natural products including three phenolic acids, two coumarins, three flavonoids, one terpene and one iridoid glycoside. All of the isolated compounds were elucidated as 2-hydroxybenzoic acid (salicylic acid), 3,4-dihdroxybenzoic acid, 2,4 dihydroxybenzoic acid, 7-hydroxy-6-methoxycoumarin (scopoletin), 3,4-dihydroxy- 7-methoxycoumarin, quercetin, kaempferol, taxifolin, loganin and /3-sitosterol. They were isolated by applying various chromatographic techniques including vacuum liquid chromatography, column chromatography, preparative thin layer chromatography as well as recycling preparative High Performance Liquid Chromatography (HPLC) while the structure elucidation of compounds were accomplished with the aid of one-dimensional (ID) and two-dimensional (2D) Nuclear Magnetic Resonance (NMR) spectral data. Further characterization of these compounds were performed with the aid of various spectroscopic methods such as Ultraviolet-Visible spectroscopy (UV-Vis), Fourier Transform Infrared (FTIR) spectroscopy and mass spectrometry (MS). In the evaluation of its in vitro antihyperglycemic potential, the crude extract, fractions and selected compounds were assayed for oglucosidase inhibitory activity. The crude methanolic stem extract of this plant exhibited high percentage of oglucosidase inhibition (87.7%), the acetone fraction exhibited strong inhibition (89.2%) while dichloromethane fraction demonstrated a moderate inhibition (75.3%) against oglucosidase enzyme at concentration of 1 mg/ml. The IC₅₀ values of both fractions were found to be much lower than the standard acarbose suggesting the presence of potential oglucosidase inhibitors. All selected compounds including 2,4-dihydroxybenzoic acid, quercetin and loganin isolated from the acetone fraction were also assayed for oglucosidase inhibitory properties and their percentage inhibition against the enzyme measured at concentration of 1 mg/ml. 2,4-Dihydroxybenzoic acid and quercetin showed strong inhibitory effect against α-glucosidase enzyme with IC₅₀ values of 549 |ig/ml (3.56 mM) and 556 ng/ml (1.84 mM), respectively, compared to the standard acarbose (IC₅₀ 580 μ/ml or 0.89 mM) whereas the iridoid glycoside loganin showed only weak oglucosidase inhibition (44.9%). Scopoletin, a major compound isolated from dichloromethane fraction also displayed a weak activity of oglucosidase inhibition (34.5%). In short, a total often chemical constituents were isolated from the stem and flower extracts of Malaysian Uncaria cordata var. ferruginea. Among them, three compounds were reported for the first time from the genus. This is also the first report on the non-alkaloidal constituents of the plant. Their in vitro anti-hyperglycemic potential have provided some scientific evidence on the traditional use of the plant for diabetes.